(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2025)
Discipline in performing congregational prayers at school is one of the key indicators in assessing the success of religious education among students. This study uses a qualitative method with a case study approach. There was a significant increase in student attendance for congregational prayers between October and November, with the number of students who received punishment decreasing from 262 to 142 after the implementation of several strategies. This indicates that, although there are strategies in place to discipline students, challenges still remain in changing students’ behavior and attitudes toward religious obligations. This research was conducted at SMA Negeri 3 Payakumbuh. The informants in this study include a religious education teacher, the vice principal for student affairs, and five students. The study reveals that the teacher applied strategies such as providing attendance records and a presence card as proof of discipline in performing the Zuhur congregational prayer, as well as administering sanctions to students who did not demonstrate discipline in carrying it out. This approach not only encourages students to regularly participate in congregational prayers but also helps foster a disciplined attitude that can positively impact other areas of life, such as in terms of study discipline and daily behavior.